Pengaruh Pandemi COVID-19 terhadap Psikologi Anak dalam Proses Belajar - Asah Arifatul Awaliyah; Asri; Yehezkiel Prayogi (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
The COVID-19 pandemic has brought significant changes to education in Indonesia, particularly in the learning process for children at the elementary school level. The transition from face-to-face to online learning has forced students to adapt to new, technology-based learning methods. This situation not only impacts the learning process but also affects children's psychological well-being during learning. This study used a quantitative method with a descriptive correlational approach to determine the impact of the COVID-19 pandemic on children's psychological well-being during learning. Data were obtained through questionnaires, observations, and documentation with student respondents participating in online learning. Data analysis was conducted using descriptive analysis and simple statistical tests using SPSS or Microsoft Excel to examine the relationship between the variables studied. The results show that online learning during the pandemic has impacted children's psychological well-being, such as decreased enthusiasm for learning, boredom, stress, and difficulty concentrating. This is influenced by a lack of social interaction, excessive use of digital devices, and limited parental guidance during the learning process at home.